Judaism Defined: Mattathias and the Destiny of His People - Scolnic, Benjamin Edidin (Hamilton Books, 2010)
Scholars have questioned every aspect of the story of Mattathias in 1 Maccabees; the revisionist narrative turns Mattathias and his Maccabees from the heroes of the Jewish holiday of Hanukkah and idealistic fighters for religious freedom, into merely ambitious men who ruthlessly strove for power and usurped the high priesthood of Judaea. Dr. Benjamin Edidin Scolnic takes a fresh, unbiased approach to every element of the story: the incident at Mode n, Mattathias's priestly credentials and their implications for his beliefs, the meaning of personal ambition and the greater ambition to create the Jewish kingdom promised by the sacred biblical texts, the meaning of circumcision in his time, and the decision to fight on the Sabbath. Mattathias's actions of zealous violence, as controversial as they were in both his day and as they often are seen today, were primarily for the preservation of his religion and people. Dr. Scolnic asserts that it was Mattathias who defined Judaism and Jewishness for his time.